Thermophilic xylanase isolated from the Xerophytic- Cereus pterogonus and Opuntia vulgaris plant sp. - Vikramathithan Jeyaraman; Nirmal Kumar Gali; Muthuraman Pandurangan; Srikumar Kotteazeth (International Journal of Phytomedicine, 2010)
A thermo stable xylanase was isolated and characterized from the cladodes of crude Cereus pterogonus and Opuntia vulgaris plant species. The enzyme was active in acidic pH 5.0 and temperature optimum for Cereus pterogonus was 60oC and 80oC, where as in the Opuntia vulgaris plant sp showed three temperature isoforms 50oC, 70oC and 90oC respectively. The metal ions 10mM Co2+, Mn2+, 5mM Ni2+ and 1mM Fe3+ showed enzyme activity at 60oC and 80oC for Cereus pterogonus plant sp, where as Opuntia vulgaris plant sp the maximum activity was observed on 50oC, 70oC and 90oC. The crude homogenate of both plant sp showed several protein bands on SDS-PAGE, but two activity bands on the zymogram analysis. The main aim of the present study was to check the xylanase activity on eukaryotic xerophytic plant sp, surprisingly the enzyme activity was observed in Cereus pterogonus and Opuntia vulgaris plant sp. This study may help protein engineers to design more efficient and acidophilic enzymes for use in different biotechnological processes. In future work the enzyme will purify and characterized for various industrial applications.